Pengaruh Tingkat PDRB Terhadap Konsumsi Rumah Tangga: Komparatif 34 Provinsi di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
Household consumption is a major component in the formation of the national Gross Domestic Product (GDP). In 2023, household consumption contributed more than half of Indonesia's GDP structure. Therefore, understanding the factors that influence household consumption is important in the context of macroeconomic growth, including how Regional Domestic Product (RDP) as an indicator of regional income affects it. In macroeconomic theory, income is the primary determinant of consumption. This study aims to test whether there is a statistically significant relationship between RDP and household consumption in 34 provinces in Indonesia in 2023, as part of efforts to understand domestic macroeconomic dynamics. The results of this study are expected to provide policymakers with an overview of the importance of regional economic growth in driving household consumption. In addition, this analysis can also serve as a basis for more equitable and sustainable economic development planning. This study uses a quantitative and qualitative descriptive analysis approach by analyzing secondary data sourced from official publications of the Central Statistics Agency (BPS) in 34 provinces in Indonesia in 2023. Data processing and analysis were carried out using SPSS software. This study concluded that in 2023, high GRDP had a positive effect on increasing household consumption. This shows that high GRDP encourages households to increase their consumption expenditure. Further research is also recommended to include additional variables so that the relationship between indicators can be analyzed more comprehensively.